2021
DOI: 10.1186/s12909-021-02840-3
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 and dental distance-based education: students’ perceptions in an Italian University

Abstract: Background The aim of the study was to analyze the perception of dental faculties students regarding the complete transition to distance-based education (DE) and the adaptation of this educational strategy, due to Covid-19 pandemic. A questionnaire to be completed anonymously was submitted online to students attending the faculties of Dentistry and Oral Hygiene at Sapienza, University of Rome, after the end of distance lessons. The collected data were processed statistically, providing descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
4
15
0
2
Order By: Relevance
“…The findings indicate that students had problems with the technical aspect of DBE (use of communication tools), organization of online lectures, and social exclusion. This is an experience that Slovenian students share with their counterparts abroad ( Almendingen et al., 2021 ; Desai et al., 2020 ; Di Giacomo & Di Paolo, 2021 ; Khan et al., 2021 ; Mishraa et al., 2020 ; Mohammed et al., 2020 ; Nadaf, 2021 ; Oloyede et al., 2021 ; Peimani & Kamalipour, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings indicate that students had problems with the technical aspect of DBE (use of communication tools), organization of online lectures, and social exclusion. This is an experience that Slovenian students share with their counterparts abroad ( Almendingen et al., 2021 ; Desai et al., 2020 ; Di Giacomo & Di Paolo, 2021 ; Khan et al., 2021 ; Mishraa et al., 2020 ; Mohammed et al., 2020 ; Nadaf, 2021 ; Oloyede et al., 2021 ; Peimani & Kamalipour, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 crisis basically plunged lecturers and students into an environment where they had to get used to what Di Giacomo and Carlo Di Paolo ( Di Giacomo & Di Paolo, 2021 ) call distance-based education (DBE). In fact, this is a teaching practice that has been imposed on people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid 19 pandemic has certainly had a huge impact on the entire educational process in the world, forcing many universities to shift traditional lecture-based learning to team-based learning [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Paola Di Giacomo.…”
mentioning
confidence: 99%